Cellular infiltrate of jejunal biopsies in adult coeliac disease in relation to gluten withdrawal. Issue 4 (April 1974) - Holmes, G. K. T.; Asquith, P.; Stokes, P. L.; Cooke, W. T.
Abstract : A comparison has been made of inflammatory cell counts in the lamina propria and epithelium of jejunal biopsies in 11 patients with adult coeliac disease with those found in 12 control subjects. In the coeliac patients, there were significant increases in the numbers of total cells, plasma cells, and intraepithelial lymphocytes, but a significant reduction in lamina propria lymphocytes. Following clinical improvement on a strict gluten-free diet, significant changes in cell counts occurred, but with the exception of lymphocytes in the lamina propria, the counts were still abnormal. Analysis of five patients in whom the biopsy improved to near normal morphology and of six in whom there was no such improvement showed that significant falls in plasma cells and rises in lymphocytes in the lamina propria could occur without improvement in other morphological appearances. These results seem relevant to the problem of diagnosing coeliac disease in patients who, on gluten withdrawal, show an unequivocal clinical response, but no gross morphological improvement in the jejunal biopsy. On the basis of the observed changes in cell counts, there seems little justification in questioning the diagnosis of coeliac disease in such patients.